Upregulation of PREX2 promotes the proliferation and migration of hepatocellular carcinoma cells via PTEN-AKT signaling - HE, SHUJIE (Oncol Lett, 2016)
Phosphatidylinositol-3,4,5-trisphosphate Rac exchanger 2 (PREX2), a regulator of the small guanosine triphosphatase Rac, demonstrates an inhibitory effect on the activity of phosphatase and tensin homolog (PTEN). Previously, PREX2 was implicated in the regulation of cell invasion in hepatocellular carcinoma (HCC). However, the exact role of PREX2 in the regulation of HCC cell proliferation and migration, as well as the underlying mechanisms, remains unclear. In the present study, reverse transcription-quantitative polymerase chain reaction revealed that PREX2 was upregulated in HCC tissue compared with matched adjacent non-tumorous tissue. In addition, the present study demonstrated that the messenger RNA and protein levels of PREX2 increased in human HCC HepG2, LH86, LMH and PLHC-1 cell lines compared with normal human liver THLE-3 cells. Overexpression of PREX2 significantly enhanced the proliferation and migration of HCC cells, and knockdown of PREX2 expression significantly suppressed the proliferation and migration of HCC cells. Additional investigation revealed that overexpression of PREX2 suppressed the activity of PTEN, leading to an enhancement in the activity of protein kinase B (AKT). By contrast, knockdown of PREX2 expression upregulated the activity of PTEN and suppressed the activity of AKT. Overall, the present study suggests that PREX2 promotes the proliferation and migration of HCC cells by inhibiting PTEN-AKT signaling.